PENGOLAHAN SAMPAH RUMAH TANGGA MENJADI ECO ENZYME SEBAGAI PUPUK DAN CAIRAN FERMENTASI SERBAGUNA DI KELURAHAN PAMAK, KECAMATAN TEBING - KABUPATEN KARIMUN - One Yantri; Nona Jane Onoyi; Ely Kurniawati; Diana Titik Windayati; Mursal; Suyanto; Nona Jane Onoyi (Jurnal Pengabdian Ibnu Sina, 2022)
Pamak is one of the villages in Tebing District, Karimun Regency, Riau Islands Province. The majority of the population are immigrants from outside the island of Karimun, who work in various fields such as government employees, teachers and employees in private companies. Meanwhile, the majority of mothers are only housewives, whose daily activities are mostly at home. This activity is very useful to increase the knowledge of mothers about the use of household waste that is produced every day from activities in the kitchen. In addition to raw materials that can be obtained easily without having to buy, because they can be obtained from the rest of the mothers' cooking activities every day, the process is also very simple and easy to do. By using these eco enzymes, mothers can save on expenses related to cleaning in their daily household activities. So many benefits that can be obtained from the Eco enzyme. Can be used as a floor cleaner, dishwasher, laundry mix, air freshener, water purifier and plant fertilizer. Those women in Pamak Village were very enthusiastic about participating in the socialization of making the eco enzyme. Mothers now understand that kitchen waste does not have to be thrown away without being used. By not spending additional costs to get raw materials, with an easy process and no special skills required, now mothers can create their own cleaners and fertilizers. And it has economic value if it is practiced because after getting the harvest at the end of the process, eco enzymes can be sold directly to consumers. So that mothers can save on kitchen expenses while also increasing their income with the knowledge about making this eco enzyme.